2007 IEEE Congress on Evolutionary Computation 2007
DOI: 10.1109/cec.2007.4424483
|View full text |Cite
|
Sign up to set email alerts
|

Gene selection in cancer classification using PSO/SVM and GA/SVM hybrid algorithms

Abstract: Abstract-In this work we compare the use of a Particle Swarm Optimization (PSO) and a Genetic Algorithm (GA) (both augmented with Support Vector Machines SVM) for the classification of high dimensional Microarray Data. Both algorithms are used for finding small samples of informative genes amongst thousands of them. A SVM classifier with 10-fold cross-validation is applied in order to validate and evaluate the provided solutions. A first contribution is to prove that P SOSV M is able to find interesting genes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
125
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(126 citation statements)
references
References 28 publications
0
125
0
1
Order By: Relevance
“…In other hand, compared with other approach Bio-Inspired evolutionary approach generally obtains one gene subset with better classification performance but much more computational cost [3]. Bio-Inspired evolutionary gene selection methods can be impractical for some computationally expensive algorithms such as SVM or artificial neural networks [2]. However, the classification accuracy in cancer research in significant, because this reason often uses Bio-Inspired evolutionary gene selection methods in cancer prediction [3].…”
Section: Analysis and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In other hand, compared with other approach Bio-Inspired evolutionary approach generally obtains one gene subset with better classification performance but much more computational cost [3]. Bio-Inspired evolutionary gene selection methods can be impractical for some computationally expensive algorithms such as SVM or artificial neural networks [2]. However, the classification accuracy in cancer research in significant, because this reason often uses Bio-Inspired evolutionary gene selection methods in cancer prediction [3].…”
Section: Analysis and Discussionmentioning
confidence: 99%
“…It offers an efficient method of gathering data that can be used to determine the patterns of gene expression of all the genes in an organism in a single experiment [1], [2]. DNA microarrays can be used to determine which genes are being expressed in a given cell type at a particular time and under particular conditions, to compare the gene expression in two different cell types or tissue samples, and then we can determine the more informative genes that are responsible to cause specific disease or cancer [3].…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, tools for decreasing the number of features in order to improve the classification or to help to identify interesting features in noisy environments are necessary. In addition, SVM can treat data with a large number of features, but it has been shown that its performance is increased by reducing the number of features [7].…”
Section: Features Classification 31 Svm Classifiermentioning
confidence: 99%
“…For non linearly separable cases, samples are mapped to a high dimensional space where such a separating hyperplane can be found. The assignment is carried out by means of a mechanism called the kernel function [7]. SVM is widely used in the domain of cancer studies, protein identification and specially in Microarray data.…”
Section: Features Classification 31 Svm Classifiermentioning
confidence: 99%
“…It needs to use computational methods in that gene expression microarray datasets are very large number of various genes in the gene datasets. It has been a challenging problem to identify the genes that are relevant or not to a clinical diagnosis [1,5,15]. As feature selection methods, mutual information [6,7,13], the t-test [14], threshold number of misclassifications (TNoM) score [8], and the Bhattacharyya distance [3,4,21] have been widely used in finding relevant genes.…”
Section: Introductionmentioning
confidence: 99%